The emptiness of business excellence : the flawed foundations of popular management theory - Collins, David, 1966-; Collins, Jack, 2002- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"In Search of Excellence was the book that launched a thousand popular management books. In this concise book, David and Jack Collins demonstrate the emptiness of business excellence and in so doing reveal the flawed foundations of popular management theory. Focusing upon the conduct of those organizations vaunted as 'exemplars of excellence' the authors build upon insightful case reports to demonstrate wholesale misconduct at the very heart of the excellence project. Indeed, The Emptiness of Business Excellence demonstrates that the exemplars of excellence indulged bribery, corruption, racism, sexism and anti-Semitism...and more besides! Furthermore, the book demonstrates that, despite their claims to knowledge, Peters and Waterman often knew little about the financial performance of their excellent organizations and were either unaware of or had chosen to overlook reports which highlighted deeply problematic conduct within those formations, which they offered as beacons for change and renewal. This book will be of interest to researchers, scholars and students with an interest in business and management, especially those focusing on the realities of managerial practice"--
Introduction: The enduring significance of In Search of Excellence. -- In Search of Excellence in Theory. -- In Search of Excellence in Practice. -- Conclusion: The emptiness of business excellence.
Keywords: Management -- Moral and ethical aspects; Business ethics; Intersectionality (Sociology); BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning